The Effect of Return on Assets and Return on Equity on Price to Book Value in Banking Sector Companies Listed on the Indonesia Stock Exchange - Komang Cindy Diah Pramesti; Tuti Dharmawati; Sulvariyani Tamburaka (Escalate : Economics and Business Journal, 2024)
This study aims to determine and analyze the effect of Return on Assets (ROA) an Return Equity (ROE) on Price to Book Value (PBV) in the banking sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. This study uses the purposive sampling method to determine the sample, resulting in 16 companies selected from 47 banking sector companies listed on the Indonesia Stock Exchange. The data collection method used is documentation. The data analysis method employed is multiple linear regression analysis using the SPSS V25 software application. The result os this study indicate that : (1) return on Assets affects Price to Book Value; (2) Return on Equity has no effect on Price to Book Value.